Metformin intake is associated with better survival in ovarian cancer. Issue 3 (3rd December 2012) - Kumar, Sanjeev; Meuter, Alexandra; Thapa, Prabin; Langstraat, Carrie; Giri, Shailendra; Chien, Jeremy; Rattan, Ramandeep; Cliby, William; Shridhar, Viji
Abstract BACKGROUND: The objective of this case‐control study was to identify any association of metformin intake with the survival of patients with ovarian cancer. METHODS: In this retrospective case‐control study, women with ovarian cancer who received metformin (cases) were compared with women with ovarian cancer who did not receive metformin (controls). A 2‐layered analysis was conducted. In preliminary analysis, all cases (the OC cohort) were compared with controls at a 1:2 ratio. Subsequently, in definitive analysis, only patients who had epithelial ovarian cancer (the EOC cohort) were compared with controls at a 1:3 ratio. In the EOC cohort, cases were matched with controls for age (±5 years), International Federation of Gynecology and Obstetrics stage, and residual disease. Prognostic variables and disease specific survival were compared using chi‐square tests, the Kaplan‐Meier (log‐rank) method, and Cox proportional hazards analysis. RESULTS: In a preliminary analysis of the OC cohort (72 cases and 143 controls), cases had better survival (5‐year disease‐specific survival for cases vs controls, 73% vs 44%; P = .0002). In the definitive analysis of the EOC cohort (61 cases and 178 controls), the distribution of age, disease stage, optimal cytoreduction, serous histology, and platinum chemotherapy remained similar between cases and controls (P > .05). Despite these similarities, cases had significantly better survival (5‐year disease‐specific survival for cases vs controls, 67% vs 47%; P = .007). On multivariate analysis, metformin remained an independent predictor of survival (hazard ratio, 2.2; 95% confidence interval, 1.2‐3.8; P = .007) after controlling for disease stage, grade, histology, chemotherapy, body mass index, and surgical cytoreduction. CONCLUSIONS: The results of this study indicated an association of metformin intake with survival in patients with ovarian cancer. The receipt of metformin was associated with better survival, and the authors concluded that metformin is worthy of clinical trials in ovarian cancer. Cancer 2013. © 2012 American Cancer Society.